1974
DOI: 10.1177/00220345740530012301
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Bond Strength Between Fissure Sealants and Enamel

Abstract: Acrylic buttons were attached to tooth enamel by in situ curing of three types of polymeric fissure sealants, a dental cement, and a glass ionomer cement and then were immersed in water. The polymeric materials exhibited the greatest bond strengths to enamel, but in two instances the bond strength decreased with time although the cements showed increased strength. One polymeric material exhibited an unchanged bond strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1974
1974
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…The forces required to separate the buttons from the enamel surfaces of the teeth for the polymeric materials Epoxylite 9075 and Nuva Seal after 4 h are given in Table 2 and (Williams et al, 1974). ns, F>0 05. of the materials and also compare bond strengths obtained using buffered acid (7 % zinc oxide) with the unbuffered acid etchants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The forces required to separate the buttons from the enamel surfaces of the teeth for the polymeric materials Epoxylite 9075 and Nuva Seal after 4 h are given in Table 2 and (Williams et al, 1974). ns, F>0 05. of the materials and also compare bond strengths obtained using buffered acid (7 % zinc oxide) with the unbuffered acid etchants.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental technique used has been described previously (Williams et al, 1974). Clear acrylic* buttons of surface area 12-57 mm^ were cemented to teeth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows the coefficient of variation and provisional classification of the complexity of the methods reported in the past. , Swartz & Phillips, 1955Lee et al, 1969,• •> Eden et al, 1970Otsuki et al, 1973Williams et al, 1974 Complexity The exact mechanism by which sealants applied to the teeth are lost under clinical conditions is not yet established, but clinical observation indicates that it is most probably an adhesive or adhesive/cohesive break at the enamel-sealant junction. This is supported by Retief (1974) who has shown that during tensile bond strength studies, spicules of adhesive remain embedded in the etched enamel surface whilst spicules of fractured enamel are retained within the interface on the adhesive side.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous methods have been described previously for measuring the tensile bond strength of dental materials to enamel (Swartz & Phillips, 1955;Bowen, 1965;Lee, Swartz & Culp, 1969;Eden, Craig & Peyton, 1970;Otsuki et al, 1973;Williams, von Fraunhofer & Winter, 1974). The accuracy achieved in adhesion tests of sealant materials to natural teeth (human or bovine) are limited by variations in the microscopic structure and composition of the enamel.…”
Section: Introductionmentioning
confidence: 99%